1990
DOI: 10.1007/bf01063621
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-mediated transport in the hepatic distribution and elimination of drugs, with special reference to the category of organic cations

Abstract: Carrier-mediated transport of drugs occurs in various tissues in the body and may largely affect the rate of distribution and elimination. Saturable translocation mechanisms allowing competitive interactions have been identified in the kidneys (tubular secretion), mucosal cells in the gut (intestinal absorption and secretion), choroid plexus (removal of drug from the cerebrospinal fluid), and liver (hepatobiliary excretion). Drugs with quaternary and tertiary amine groups represent the large category of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 148 publications
0
43
0
Order By: Relevance
“…It has been observed that some cationic drugs, including propranolol and imipramine, may undergo cellular uptake by active transport (Meijer et al, 1990;Nakamura et al, 1994;van Montfoort et al, 2003;Chandra and Brouwer, 2004) involving members of the organic anion-transporting polypeptide and organic cation transporter families. It is of interest that the uptake of imipramine was not affected by treatment with rotenone, an inhibitor of ATP-dependent transport (consistent with the involvement of solute-linked carrier organic anion transporter rather than the ATP-binding cassette subfamily C family of transporter proteins).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that some cationic drugs, including propranolol and imipramine, may undergo cellular uptake by active transport (Meijer et al, 1990;Nakamura et al, 1994;van Montfoort et al, 2003;Chandra and Brouwer, 2004) involving members of the organic anion-transporting polypeptide and organic cation transporter families. It is of interest that the uptake of imipramine was not affected by treatment with rotenone, an inhibitor of ATP-dependent transport (consistent with the involvement of solute-linked carrier organic anion transporter rather than the ATP-binding cassette subfamily C family of transporter proteins).…”
Section: Discussionmentioning
confidence: 99%
“…However, renal secretion of vecuronium contributed only minimally to the total body elimina- tion of the type 2 cationic compound as compared with the smaller type 1 cationic drugs; this finding is in accordance with those of other studies. 15,39,40 The exact role of P-glycoprotein in the kidney, with regard to renal drug secretion, is still under investigation both in vivo and in vitro. 19,[41][42][43] The contribution of P-glycoprotein to renal drug elimination may in part be obscured by an abundant presence of other transport mechanisms in the proximal tubule kidney cells that also contribute to renal secretion of cationic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays a central role in the disposition of exogenous and endogenous compounds [ 18,191. Primary-active ATP-dependent transport is the major mechanism to secrete toxic and non-toxic, exogenous as well as endogenous substances across the hepatocyte canalicular membrane into bile [4,6,15,.…”
Section: P-glycoproteinmentioning
confidence: 99%